Laporan Kasus: Proses Asuhan Gizi Terstandar pada Pasien Miastenia Gravis dengan Disfagia dan Malnutrisi: Case Report: Nutrition Care Process in a Patient with Myasthenia Gravis, Dysphagia, and Malnutrition - Karuniawati, Fatimah; Dewi, Mira (Jurnal Ilmu Gizi dan Dietetik, 2025)
Myasthenia gravis is a chronic autoimmune neuromuscular disorder characterized by impaired transmission at the neuromuscular junction, resulting in fluctuating skeletal muscle weakness. Oropharyngeal muscle involvement frequently causes dysphagia, which can significantly impair oral intake and increase the risk of malnutrition. This case report describes the implementation of the Nutrition Care Process (NCP) in a patient with myasthenia gravis complicated by dysphagia and severe malnutrition, as defined by the Global Leadership Initiative on Malnutrition (GLIM) criteria, and evaluates changes in nutritional and clinical status during hospitalization. The patient was a 36-year-old male presenting with severe malnutrition, evidenced by a 42% unintentional weight loss over 16 months and a body mass index (BMI) of 12.58 kg/m². Nutritional management was initiated progressively, beginning with enteral nutrition via a nasogastric tube, followed by a gradual transition to combined enteral and oral feeding according to swallowing function and gastrointestinal tolerance. Nutritional interventions and patient responses were monitored over an 18-day hospitalization period using anthropometric measurements, biochemical parameters, clinical assessments, and dietary intake evaluation. Energy intake was gradually increased from 1,500 kcal/day to 2,100 kcal/day, while protein intake rose from 71 g/day to 89 g/day. No clinical or biochemical signs of refeeding syndrome were observed throughout the intervention. Improvements in nutritional intake were accompanied by a 2 kg increase in body weight, resulting in an increase in BMI to 13.15 kg/m². Clinical outcomes also improved, as indicated by a reduction in the Myasthenia Gravis Composite Score from 6 to 2, reflecting enhanced swallowing function and neuromuscular strength. This case underscores the importance of individualized, progressive nutritional management supported by interdisciplinary collaboration in improving nutritional status and clinical outcomes in patients with myasthenia gravis and dysphagia. Appropriate implementation of the Nutrition Care Process plays a crucial role in supporting recovery and optimizing quality of life in this vulnerable population.